Miss Julia lays down the law : a novel - Ross, Ann B. (Ross, Ann B. Miss Julia series., 2015)
"It's November and Miss Julia is looking forward to some quiet time before the holidays. That is until snobby Connie Clayborn and her rich husband move to town. At first, Miss Julia and the other ladies are pleased to be invited over for coffee, but the afternoon turns into a slap in the face when their hostess spouts nonstop criticism about Abbotsville. Why, how dare she? Days later, Miss Julia decides to confront Connie woman to woman, but when she arrives, Connie is lying on the kitchen floor-lifeless in a pool of blood. Who could have done this? Miss Julia will need to find out fast-particularly because her fingerprints are now all over the crime scene"--